Legal Protection Of MSME Trademarks As A Pillar Of Local Economic Justice - Sultan, Rahmadaniyah; Junus, Nirwan; Fazri Elfrikri, Nurul (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The legal protection of trademarks for Micro, Small, and Medium Enterprises (MSMEs) in Pohuwato is an increasingly urgent issue in light of the sector’s rapid growth and contribution to the local economy. Despite the existence of Law No. 20 of 2016 on Trademarks and Geographical Indications, which provides a clear legal framework for trademark registration and protection, a large number of MSME actors in the region have not registered their trademarks. This is largely due to a lack of legal awareness, the perception that registration costs are too high, and the belief that the process is too complex or unnecessary for small businesses. The objective of this research is to analyze how trademark protection for MSMEs is implemented in Pohuwato, to understand the legal consequences of unregistered trademarks, and to evaluate the role of government institutions in facilitating registration. The research employs an empirical legal method with a qualitative approach, using data gathered through interviews, field observations, and questionnaires distributed to 100 MSME respondents. The findings reveal that although the local government and the Regional Office of the Ministry of Law and Human Rights in Gorontalo have made substantial efforts such as door-to-door socialization campaigns and registration facilitation the overall rate of trademark registration remains low. The legal consequence of not registering a trademark is the absence of exclusive rights and the inability to take legal action against infringement, which may result in financial loss and reputational damage. This research concludes that consistent legal education and expanded outreach programs across all districts in Pohuwato are essential to enhance MSMEs' legal awareness and strengthen their legal protection.